The detection and distribution of antidepressants in biological specimens - Nemecek, Cene? (My University, 2024)
This study developed and validated a method utilizing Ultra-Performance Liquid Chromatography (UPLC) paired with tandem mass spectrometry (MS-MS) to detect and quantify thirteen antidepressants and metabolites in blood and various biological tissue samples from deceased pilots whose specimens were sent to the Federal Aviation Administration (FAA) for toxicological analysis following autopsy. Validation was conducted using a modified version of American National Standards Institute/American Academy of Forensic Science Standards Board (ANSI/ASB) Standard 036, and included a calibration model, limit of detection, carryover, cross contribution, dilution integrity, drug interference, bias and precision, fluid and tissue controls, ion suppression/enhancement, recovery, process efficiency, stability, and measurement of uncertainty. Using a linear dynamic range of 200 times the lowest cutoff concentration, all analytes and matrices were successfully validated. Analytes were found to be stable at 4?C for at least four days, through at least three freeze/thaw cycles at -20?C, and on the instrument autosampler (10?C) for at least four days. Once this method was successfully developed and validated, Phase II consisted of a postmortem distribution study that examined citalopram and its N-desmethyl metabolite to determine the feasibility of relating a tissue drug concentration to the blood concentration, as well as a metabolite to drug ratio. The only correlations that could be established were the citalopram brain:blood ratio at 8.3 and the citalopram muscle:blood ratio at 1.6. Though other correlations were not established, notable trends were observed. Liver and lung had the highest concentrations of drug and metabolite, while spinal fluid and vitreous had the lowest. No metabolite to drug ratio correlation was established, although bile appeared to have the highest ratio at 1.3 while all other specimens were below 0.5, indicating a low concentration of metabolite present compared to the parent drug.
Keywords: Antidepressants--Analysis; Air pilots; Diagnostic specimens; Forensic toxicology--Methodology; Aviation toxicology; Antidepressant; Aviation; Chemistry; Forensic; Postmortem; Toxicology